First-line therapy: insights from a real-world analysis of cryoablation in patients with atrial fibrillation. Issue 8 (August 2021) - Moltrasio, Massimo; Iacopino, Saverio; Arena, Giuseppe; Pieragnoli, Paolo; Molon, Giulio; Manfrin, Massimiliano; Verlato, Roberto; Ottaviano, Luca; Rovaris, Giovanni; Catanzariti, Domenico; Cipolletta, Laura; Nicolis, Daniele; et al.
Abstract : Aims: Pulmonary vein isolation (PVI) using cryoballoon ablation (CBA) is mainly reserved for patients with drug-refractory or drug-intolerant symptomatic atrial fibrillation. We evaluated a large cohort of patients treated in a real-world setting and examined the safety and efficacy profile of CBA when applied as a first-line treatment for atrial fibrillation. Methods: In total, 249 patients (23% women; 56 ± 13 years; mean left atrial diameter 41 ± 7 mm; 73.5% paroxysmal atrial fibrillation; and 26.5% persistent atrial fibrillation) underwent an index PVI by CBA. Data were collected prospectively in the framework of the 1STOP ClinicalService project, involving 26 Italian cardiology centers. Results: Median procedure and fluoroscopy times were 90.0 and 21.0 min, respectively. Acute procedural success was 99.8%. Acute/periprocedural complications were observed in seven patients (2.8%), including: four transient diaphragmatic paralyses, one pericardial effusion (not requiring any intervention), one transient ischemic attack, and one minor vascular complication. The Kaplan--Meier freedom from atrial fibrillation recurrence was 86.3% at 12 months and 76% at 24 months. Seventeen patients (6.8%) had a repeat catheter ablation procedure during the follow-up period. At last follow-up, 10% of patients were on an anticoagulation therapy, whereas 6.8% were on an antiarrhythmic drug. Conclusion: In our multicenter real-world experience, PVI by CBA in a first-line atrial fibrillation patient population was well tolerated, effective, and promising. CBA with a PVI strategy can be used to treat patients with paroxysmal and persistent atrial fibrillation with good acute procedural success, short procedure times, and acceptable safety. Clinical Trial Registration: clinicaltrials.gov (NCT01007474).